Influence of partial replacement of cement by ceramic powder and addition of steel fibers on the mechanical properties of concrete - Karolay Alegre Cornelio, Mayra (2024)
Cement production is a significant source of CO2 emissions, playing a crucial role in climate change. Consequently, reducing the cement content in concrete mixes represents a considerable challenge for researchers, who seek to replace it with recycled materials and reduce dependence on natural resources. This experimental study focuses on exploring the feasibility of partially replacing cement with ceramic tile powder and incorporating steel fibers to improve the mechanical properties of concrete. Three mixtures of 280 kg/cm2 of characteristic resistance were designed: a concrete pattern (P01), one with 5% replacement of Portland cement with ceramic powder and 1.5% fibers (PC5F1.5), and another with 10% replacement. and 1.5% fibers (PC10F1.5). Slump and air content tests were carried out on the fresh concrete mixes, revealing a decrease in workability with increasing cement replacement. However, these changes remained within acceptable limits. In addition, compression, tensile and flexural strength tests were carried out at ages of 7, 14 and 28 days. The results highlighted the superior performance of the PC5F1.5 mixture, which showed a significant increase of 18% in tensile strength and 11% in flexural strength compared to the concrete pattern at 28 days. In the case of the PC10F1.5 mix, more moderate increases of 8.5% and 3% in tensile and flexural strength, respectively, will be observed, but a 4% reduction in compressive strength will be recorded. In conclusion, it is considered that the replacement of cement with ceramic powder and the incorporation of steel fibers have a positive impact on the mechanical properties of the concrete, especially highlighting the mixture with a replacement of 5% Portland cement.